a)\(x^2+5y^2-2xy+4y+1=0\)
\(x^2+2xy+y^2+4y^2+4y+1=0\)
\(\left(x+y\right)^2+\left(2y+1\right)^2=0\)
\(\Rightarrow\hept{\begin{cases}x+y=0\\2y+1=0\end{cases}\Rightarrow}\hept{\begin{cases}x=-y\\y=-\frac{1}{2}\left(1\right)\end{cases}}\)
Từ (1) ta đc: x = 1/2
b)\(5x^2+5y^2+8xy-2x+2y+2=0\)
\(4x^2+8xy+4y^2+x^2-2x+1+y^2+2y+1=0\)
\(\left(2x+2y\right)^2+\left(x-1\right)^2+\left(y+1\right)^2=0\)
\(\Rightarrow\hept{\begin{cases}2x+2y=0\\x-1=0\\y+1=0\end{cases}\Rightarrow}\hept{\begin{cases}x=-y\\x=1\\y=-1\end{cases}}\)
CÂU B Sao bạn làm được vậy
Bài làm:
a) \(x^2+5y^2-2xy+4y+1=0\)
\(\Leftrightarrow\left(x^2-2xy+y^2\right)+\left(4y^2+4y+1\right)=0\)
\(\Leftrightarrow\left(x-y\right)^2+\left(2y+1\right)^2=0\)
Vì \(\hept{\begin{cases}\left(x-y\right)^2\ge0\\\left(2y+1\right)^2\ge0\end{cases}}\)\(\Rightarrow\hept{\begin{cases}\left(x-y\right)^2=0\\\left(2y+1\right)^2=0\end{cases}\Rightarrow}x=y=-\frac{1}{2}\)
Vậy \(x=y=-\frac{1}{2}\)
b) \(5x^2+5y^2+8xy-2x+2y+2=0\)
\(\Leftrightarrow\left(4x^2+8xy+4y^2\right)+\left(x^2-2x+1\right)+\left(y^2+2y+1\right)=0\)
\(\Leftrightarrow4\left(x+y\right)^2+\left(x-1\right)^2+\left(x+1\right)^2=0\)
Vì \(\hept{\begin{cases}4\left(x+y\right)^2\ge0\\\left(x-1\right)^2\ge0\\\left(y+1\right)^2\ge0\end{cases}}\)\(\Rightarrow\hept{\begin{cases}4\left(x+y\right)^2=0\\\left(x-1\right)^2=0\\\left(y+1\right)^2=0\end{cases}\Rightarrow\hept{\begin{cases}x=1\\y=-1\end{cases}}}\)